Hybrid Public Speaking Model for Designing English Materials for Islamic Communication and Broadcasting Department Students (Proceeding of Dakwah Saizu International Conference, 2023)
English has big role for Communication department students. This study aims to identify the materials of public speaking as English materials and analyze the hybrid public speaking model that fulfill the Islamic Communication and Broadcasting Department students’ need. This article is a part of Research and Development (R&D). The participants of this research are the students of Islamic and Communication Broadcasting Department, Da’wah and Islamic Communication Faculty, Institut Agama Islam Negeri Kudus. The result of research stated the several typical methods for delivering hybrid public speaking model are Rotation Model, Enriched Virtual Model, Face-to-face/Online Driver Model, Flex Learning Model, Flipped Classroom Learning Model, Project Based Learning Model, and Inside-Out/Outside-In learning model